Introduction - Filippidou, Faidra (A+BE | Architecture and the Built Environment, 2018)
The rapid growth of urban areas has led to the unsustainable use of resources (Langeweg et al. 2000; Bhatta 2010; UN 2014). The impacts of urban areas are evident in regions which supply cities with food, water, energy and absorb pollution and waste (UN 2014). At the same time, the current world population, of 7.6 billion, is predicted to reach 8.6 billion in 2030 and 9.8 billion in 2050 (UN 2017). Moreover, the urban population, in 2014, accounted for 54% of the total global population. This signifies a 20% increase since 1960. In 2014, the majority of people - 54% - were living in urban areas and this percentage is estimated to rise in the future (WHO 2017). In Europe, 72.5 % of European Union (EU)-28 countries inhabitants lived in cities, towns and suburbs in 2014 (Eurostat 2016b). Nevertheless, differences between countries exist. Figure 1.1 shows the urban population growth of the Netherlands in comparison to the EU, Germany, Spain, France, Slovenia and Sweden. The Netherlands is characterised by a high level of population density and a high share of urban land use, whereas in most of the Scandinavian countries and Spain much lower levels of urban land use are present (Eurostat 2016b). In this context, the main challenge is to accommodate a greater number of people while reducing the impacts on the environment, which are the main cause for climate change (IPCC 2014). Relatedly, the improvement of the quality of life of city residents is a priority (EEA 2015). Households have a large impact on energy intensity and final energy consumption, as Figure 1.2 shows. The energy intensity3 of households, depicted on the left hand side of Figure 1.2, is increasing and at the same time 25.4% of the final energy consumption in the EU 28 was attributed to the sector in 2015 (24.8% in 2016), shown on the right hand side of Figure 1.2 (EEA 2013; Eurostat 2016a). The potential for energy consumption reduction of households is large and is set as a key priority in the policy goals and directives by the European Commission (Paulou et al. 2014; Saheb et al. 2015). One of the most prominent ways to reduce the energy consumption of residential dwellings is through energy renovations.